The inner clock—Blue light sets the human rhythm. Issue 12 (2nd September 2019) - Wahl, Siegfried; Engelhardt, Moritz; Schaupp, Patrick; Lappe, Christian; Ivanov, Iliya V.
Abstract: Visible light synchronizes the human biological clock in the suprachiasmatic nuclei of the hypothalamus to the solar 24‐hour cycle. Short wavelengths, perceived as blue color, are the strongest synchronizing agent for the circadian system that keeps most biological and psychological rhythms internally synchronized. Circadian rhythm is important for optimum function of organisms and circadian sleep–wake disruptions or chronic misalignment often may lead to psychiatric and neurodegenerative illness. The beneficial effect on circadian synchronization, sleep quality, mood, and cognitive performance depends not only on the light spectral composition but also on the timing of exposure and its intensity. Exposure to blue light during the day is important to suppress melatonin secretion, the hormone that is produced by the pineal gland and plays crucial role in circadian rhythm entrainment. While the exposure to blue is important for keeping organism's wellbeing, alertness, and cognitive performance during the day, chronic exposure to low‐intensity blue light directly before bedtime, may have serious implications on sleep quality, circadian phase and cycle durations. This rises inevitably the need for solutions to improve wellbeing, alertness, and cognitive performance in today's modern society where exposure to blue light emitting devices is ever increasing. Abstract : Light is playing an important role beyond vision. The review summarizes the current and most recent knowledge on the role of light around 470 nm and its role in circadian rhythm. The circadian rhythm is essential for life. If it is not preserved, serious diseases might develop. Light and its role in synchronization, but also in disruption of the circadian rhythm is discussed.